Late antique clay lamps from Campania: the evidence from a site on the north slope of Mt. Vesuvius - Castaldo, Vincenzo (Rei Cretariae Romanae Fautorum Acta, 2017)
Current scholarship on the late antique economy of Campania still shows a certain discrepancy between the sites on the coast and those in the hinterland. This problem is noticeable also and especially in the analysis of the pottery assemblages, for which in the majority of the cases only scattered evidence has been published so far. More extensive datasets are available solely for Neapolis, from the earlier studies by Paul Arthur at the Complesso dei Girolamini and Carminiello ai Mannesi to the more recent works at Piazza Municipio and at the Theatre.